Immunological impairment as a marker of 4-nonylphenol induced stress - SHARMA, MADHU; CHADHA, POOJA (The Indian Journal of Animal Sciences, 2019)
The goal of the current study was to evaluate different haematological parameters in order to assess the toxic effects of 4-nonylphenol (NP) on Channa punctatus after sub-chronic exposure of 90 days and recovery ascertained after 30 days. Three sublethal concentrations of 4-NP were decided after calculating the safe application rate (SAR). Furthermore, subchronic exposure to sub-lethal concentration was given for 90 days and an experiment was performed later to assess the recovery capacity of fish exposed to sub-lethal concentrations of 4-NP when kept in water without 4-NP for 30 days. Hb, PCV, RBC count, MCH (mean corpuscular haemoglobin) and MCV (mean corpuscular volume) decreased significantly with time and concentration. While WBC count increased with exposure and time. MCHC initially showed a decrease and then an increase with changing concentration level. Recovery experiment showed a great recovery of all the parameters after 30 days and values almost reached the normal level. 4-NP was toxic to C. punctatus and the study highlighted the immunological parameters as markers of stress.